Mediation across Borders - CHUA, Eunice (Institutional Knowledge at Singapore Management University, 2016)
Mr L is the director of InVisions, alarge Indonesian manufacturer providing top-of-the-range camera components toMK Pte Ltd, a Korean-headquartered mobile phone manufacturer. Mr K, who is anative Korean, is the General Manager of the company’s regional office based inThailand and manages the deals involving InVisions. The business relationshipis a lucrative one and both companies have had generally good relations since2003. Annual profits for InVision arising from sales to MK amounted to US$2.3million last year while the sales of MK’s mobile phones that are installed withInVision’s cameras reaped them a profit of US$3.5 million in the same period.During discussions for a renewal of the supplycontract in May 2012, cultural and other differences in opinion resulted in thebeginnings of a dispute emerging. Mr L expected to continue to receiveimmediate payment of the goods upon receipt as per previous practice. Mr Kproposed that payment be partially made within 30 days of the invoice date, andthe remaining payment disbursed upon reaching an agreed annual sales target inDecember each year. The rationale for this change was because the financialsituation of MK had deteriorated with increasing competition requiring morecomplicated products. MK now required a longer payment runway with all theirsuppliers. Mr K does not tell Mr L this as he felt it would weaken his negotiatingposition. The new proposal seemed risky for Mr L, and he preferred the originalarrangement. but as MK has been a reliable and important client of InVisions,he agreed to it without raising too much concern.